Membangun Sekolah Hijau Melalui Edukasi Pengolahan Sampah Organik Menjadi Ekoenzim - Tahar, Musrifah; Hidayah, Nurul; Wahid, Masyitha; Muis, Nurmuliayanti (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2025)
Ecoenzymes are liquids produced by fermenting organic waste such as vegetable and fruit scraps with sugar and water. This fermentation process produces enzymes that are useful in everyday life. The purpose of this activity is to provide knowledge and practical skills to students in managing household organic waste into ecoenzymes. This service activity was carried out at SMA N 1 Tinambung involving 20 students. The implementation activities were carried out through material presentation which included an explanation of the basic concepts of ecoenzymes, the materials needed, and the manufacturing process. The results of this activity showed an increase in students' knowledge and skills in processing organic waste, namely ecoenzyme. Students also showed high enthusiasm and interest in applying the knowledge gained in their respective homes with a score of 4.45. This activity also provided direct benefits to the training participants with a score of 4.55. This activity succeeded in increasing environmental awareness among students, as well as encouraging them to contribute to sustainable waste management efforts.